Author Correction: Hot carrier cooling mechanisms in halide perovskites - Jianhui Fu (Nature Portfolio, 2018)
The original version of this Article omitted an affiliation of Cheng Hon Alfred Huan: ‘Institute of Materials Research and Engineering (IMRE), A*STAR, 2 Fusionopolis Way, Innovis #08-03 138634, Singapore’. This has now been corrected in both the PDF and HTML versions of the article.